Peran Strategis Mangrove Dalam Pembentukan Kedaulatan Wilayah: Analisis Terhadap Ekspansi Teritorial dan Keberlanjutan Maritim - Mahesswara, Kadek Bayu Prabha; Abdul Rivai Ras; Panji Suwarno; Pujo Widodo (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
In efforts to assert maritime sovereignty and security, the strategy of managing maritime resources, particularly mangrove ecosystems, plays a crucial role. This research aims to examine the impact of national mangrove belt thickening on the expansion of a country's sovereign territory, linking maritime security aspects with sustainable maritime resource management. Through a literature study methodology, this research collects and analyzes secondary data from various scientific publications, government reports, and other relevant documents to understand the relationship between mangrove rehabilitation and territorial expansion. The findings of this analysis indicate that mangrove belt thickening has significant potential in expanding the land area of an island through natural accretion mechanisms. Consequently, this process not only strengthens the country's position in claiming maritime sovereignty but also contributes to efforts to adapt to climate change and mitigate the risk of rising sea levels. Furthermore, mangrove rehabilitation is recognized as a strategic step that supports the sustainability of fisheries resources and preserves stable coastal ecosystems. The results of this research provide important insights for policymakers, coastal area managers, and research communities in the field of maritime security. The policy recommendations generated offer guidelines for planning and executing mangrove rehabilitation programs on a national scale. This emphasizes the need for an integrated approach between maritime resource management and maritime security policies, suggesting the application of ecosystem concepts in policy development. Thus, this research not only enriches the literature in the field of maritime security with empirical evidence regarding the benefits of mangrove belt thickening but also underscores its strategic contribution to expanding a country's territorial jurisdiction.